Secret empires How the American political class hides corruption and enriches family and friends - Schweizer, Peter (New York Blackstone Audio, 2018)
Corruption has created a crisis of confidence in our government. In recent surveys, three out of four Americans believe that there is ''widespread government corruption,'' and only nineteen percent of the American people trust the federal government to do the right thing.
Keywords: Corruption